Real-world accuracy of SARS-CoV-2 antigen detection compared with qPCR: A cross-sectional study in Toledo - PR, Brazil - Carla Adriane Royer; Regis Goulart Rosa; Maicon Falavigna; Jaqueline Carvalho de Oliveira; Mariana Motta Dias da Silva; Carolina Gracia Poitevin; Hellen Abreu; Valter Antonio Baura; Ana Claudia Bonatto; Daniela Fiori Gradia; Cristina de Oliveira Rodrigues; Rafael Messias Luiz; et al. (Brazilian Journal of Infectious Diseases)
Rapid Antigen Tests (Ag-RDTs) for the detection of SARS-CoV-2 is an important diagnostic tool for containing virus spread. However, their accuracy ‒ the proportion of correct results (both true positives and true negatives) ‒ still needs to be proven when used in a real large-scale context. Accordingly, we provide data from a cross-sectional study conducted in Toledo - PR, Brazil, on the accuracy of rapid tests compared with qPCR within the Brazilian Unified Health System. A total of 2882 thousand individuals presenting symptoms suggestive of COVID-19 were screened. Overall, the antigen tests showed a sensitivity, specificity, and accuracy of 59 % (0.56‒0.62), 99 % (0.98‒0.99), and 82 % (0.81‒0.84) respectively. However, a significant difference was found when analysing two brand tests individually. In addition, for patients with a low quantification Cycle (Cq) < 20 (which indicates a high viral load), the agreement between test results was high (90.85 %). However, this agreement decreased significantly when the viral load decreased, dropping to 5.59 % for samples with Cq ≥ 33, which indicates a lower viral load. While rapid antigen tests are a valuable tool in combating virus spread, their accuracy can vary significantly between manufacturers and under conditions of low viral load.